Germination and seedling growth enhancement of Timur seed (Zanthoxylum armatum) by using cold atmospheric pressure plasma - Dahal, Samjhana; Chalise, Roshan; Khanal, Raju (BIBECHANA, 2026)
Plasma, often called the fourth state of matter, is an ionized gas with wide applications in physics ranging from astrophysical phenomena and nuclear fusion research to material processing, biomedical technologies, and modern agricultural practices. This study investigates the application of cold atmospheric pressure plasma (CAPP) for improving the wettability, seedling growth, and chlorophyll content in the leaves of Timur seeds (Zanthoxylum armatum), a medicinally and culinarily valuable Himalayan plant. We have employed gliding arc discharge for direct seed treatment, while the plasma-activated water (PAW) was generated using dielectric barrier discharge. The results reveal that direct plasma exposure had limited germination enhancement under laboratory conditions, whereas PAW significantly improved seedling growth, chlorophyll, and root–shoot development. Plasma diagnostics confirmed the formation of reactive oxygen and nitrogen species, with favorable physicochemical changes in PAW. The findings demonstrate the promising potential of CAPP for sustainable agrotechnological applications.